2003
DOI: 10.1046/j.1468-1293.2003.00157.x
|View full text |Cite
|
Sign up to set email alerts
|

Quality of generalist vs. speciality care for people with HIV on antiretroviral treatment: a prospective cohort study

Abstract: A well-working system offers high-quality healthcare to persons living with HIV, where existing teams of specialty and primary health-care professionals efficiently and effectively co-operate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(45 citation statements)
references
References 28 publications
0
45
0
Order By: Relevance
“…This view was supported by another two prospective cohort studies. Page et al, (2003) examined quality of generalist vs. specialty care for people with HIV on antiretroviral treatments and Smith et al, (1996) explored the development and evaluation of a model of health care for HIV positive patients involving specialist, hospital based teams and primary care health teams. Page et al, (2003) found that general practitioners can provide equally adequate care with access to knowledge specific to HIV treatment.…”
Section: Empirical Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…This view was supported by another two prospective cohort studies. Page et al, (2003) examined quality of generalist vs. specialty care for people with HIV on antiretroviral treatments and Smith et al, (1996) explored the development and evaluation of a model of health care for HIV positive patients involving specialist, hospital based teams and primary care health teams. Page et al, (2003) found that general practitioners can provide equally adequate care with access to knowledge specific to HIV treatment.…”
Section: Empirical Studiesmentioning
confidence: 99%
“…Page et al, (2003) examined quality of generalist vs. specialty care for people with HIV on antiretroviral treatments and Smith et al, (1996) explored the development and evaluation of a model of health care for HIV positive patients involving specialist, hospital based teams and primary care health teams. Page et al, (2003) found that general practitioners can provide equally adequate care with access to knowledge specific to HIV treatment. This was supported in Smith et al', (1996: 419) work who went to great lengths to point out that, '[their] aim was not to turn general practitioners into experts in HIV medicine who could then initiate and supervise specialist treatment regimes.…”
Section: Empirical Studiesmentioning
confidence: 99%
“…Twelve studies addressed the prevention of infectious diseases, especially influenza by providing vaccinations [11][12][13][14][15][16][17][18][19][20][21][22] or by performing a specific diagnostic test. 22 For clinical topics, most prevention activities addressed cardiovascular disease prevention, [23][24][25][26][27][28][29][30] cancer screening, [31][32][33][34] HIV, [35][36][37] prevention of osteoporosis, 38,39 addiction prevention, 40,41 and others [42][43][44][45][46][47] (Table 2). The most common observed intervention was counseling on lifestyle changes with twelve studies.…”
Section: Description Of Studiesmentioning
confidence: 99%
“…[10][11][12][13][14][15][16][17][18] There is increasing recognition that the management of HIV requires a primary care presence, but we have a poor understanding of how to integrate HIV-specific expertise within a primary care context. 7,10,[14][15][16][17][18][19][20][21] Overall, it has been difficult to distinguish the respective contributions of physician qualification and physician experience of care to the effectiveness of HIV care. 3 We have previously used routinely collected administrative data to develop and characterize an intuitive typology of shared care for people with HIV based on actual patterns of care.…”
Section: Introductionmentioning
confidence: 99%